Learning strategies on ecosystem concepts and environmental change: A pedagogical study analysis - Zuliande Zidan; Maftuhah Maftuhah; Diana Yusti; Riandi Riandi; Kusnadi Kusnadi; Adi Rahmat (Department of Biology Education, Universitas Pendidikan Indonesia, 2023)
Human activity is one of the causes of environmental damage on earth. Prevention of environmental damage can be done by increasing ecological knowledge, problem-solving skills, and attitudes such as sustainability insights and environmental awareness. One way to improve these competencies is by learning about ecosystems and environmental change. This study aims to map out effective strategies for teaching ecosystems and environmental materials so that it can more optimally develop the expected competencies. The literature review method is used to map the learning strategies used to analyze patterns of effective strategy tendencies. Literature reviews were analyzed from scientific publications indexed by Google Scholar in the 2014-2023 range. The results of the analysis show that learning about ecosystems and environmental change is recommended (1) integrating technology; (2) raising the potential of local wisdom; (3) based on contextual problems; (4) improving problem-solving skills, ecological literacy and sustainable awareness; and (5) in the form of active learning. The recommended learning strategies for ecosystem materials and environmental change are environmental approaches and process approaches, problem-based learning models, learning methods in practice or field studies, and learning media in the form of real objects or phenomena that can be analyzed by students.